الظواھر اللغویة في شعر ھارون بن موسى الرَّمادي (Journal of the College of Education for Women, 2019)
The Andoluosian literatures has been captured my mind, and had a verypure and great place in my spirit, which is remembering me the roots ofgenuine Arabic civilization spread during eight century in endoluos region.also the Arabic creation which is moved from east to far way land in thatages. And very clearly appearance tremendous men interested in science andall kind of literature and arts especially in poetry, no one who has taste andminimum knowledge can denied the effect of indoluosan prosperity amongreaders. So for that reason I work very hard to choose a very famous poet hisnick name (Al-Ramadee) he is Youseif Bin Haroon born in the first decadeof the 4TH hijri (Islamic Calendar), died in (403H). He was one student ofvery popular linguistic called abee Ali Al-qalee.They called him Almotanabee of his place also they said "poem startedfrom Kenda and sealed in Kenda" they intended Emraa Al-Kayas,Al-Motanabee and Al-Ramadee.and for all of that I preferred to search aboutthe language phenomena and the expansion in his poetry as well as someglance which focus to reveal about his huge linguistics and literaturesheritage capacity.I divided this study to three levels:- grammatical level: dialed with odd linguistic words and converse. structural level: dialed with preferment, retardation, cancellation, thelinguistic methods and the aims. laterally level: dialed with laterally acceptance, verbalism synonymyand analytic.Finally, conclusion, results that I have got in this study.